Low doses of imidacloprid induce neurotoxic effects in adult marsh frogs: GFAP, NfL, and angiostatin as biomarkers - Yermolenko, S. V.; Nedzvetsky, V. S.; Gasso, V. Y.; Spirina, V. A.; Petrushevskyi, V. B.; Kyrychenko, V. V. (Regulatory Mechanisms in Biosystems, 2022)
Imidacloprid is one of the most widely used insecticides in the world. The neurotoxicity of imidacloprid in adult amphibians has not been studied thoroughly. We investigated the expression of glial fibrillary acidic protein (GFAP), neurofilament light chain (NfL) and angiostatin in the amphibian brain to identify valid biomarkers of low dose imidacloprid exposure. For the experiment, 30 individuals of the marsh frog Pelophylax ridibundus were selected. The amphibians were divided into five groups. The duration of the experiment was 7 and 21 days. The exposure concentrations were 10 and 100 µg/L. The results of the study revealed a decrease in the expression of GFAP after 7 days in the exposure groups of 10 and 100 μg/L. An increase in the level of NfL was observed in the group exposed to 10 μg/L after 21 days of the experiment. The angiostatin level was increased after 7 days at 10 µg/L and after 21 days at 100 µg/L. The data obtained indicate that low concentrations of imidacloprid can cause neurotoxic effects in the brain of P. ridibundus. Such effects can have a significant impact on amphibian populations. According to the results of the study of the expression level of GFAP, NfL and angiostatin, it can be stated that imidacloprid has a neurotoxic effect on adult marsh frogs. The studied indicators can be promising biomarkers of environmental pollution by neonicotinoids.